Reviving a forgotten custom : an evaluation of a community based mentoring intervention - the Jamestown USIKO Youth Project - Fabrik, Carmen Janine (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MA (Psychology))--University of Stellenbosch, 2007.